Oscillation Results for Second-Order Nonlinear Damped Dynamic Equations on Time Scales - Yang-Cong Qiu; Qi-Ru Wang (Abstract and Applied Analysis)
This paper is concerned with second-order nonlinear damped dynamic equations on time scales of the following more general form (p(t)k1(x(t),xΔ(t)))Δ+r(t)k2(x(t),xΔ(t))xΔ(t)+f(t,x(σ(t)))=0. New oscillation results are given to handle some cases not covered by known criteria. An illustrative example is also presented.